Accessing communication: An analysis of the quality of RTVE’s automatic live subtitles - Iglesias-Pérez, Ana (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2025)
Nowadays, deaf and hard-of-hearing viewers should have equal access to audiovisual media and, likewise, the promotion of Galician as a minoritised language should be key for public broadcasters. Therefore, both of them should be compatible, allowing viewers with and without hearing impairments to have access to audiovisual contents in Galician. This paper presents the results of the assessment of the quality of the automatic subtitles being tested in the territorial news programs broadcast by RTVE Spanish TV channel in Galicia and considers the harmonisation of accessibility and standardisation in Galician subtitling. The analysis consisted of 10 five-minute samples in Galician and it was carried out by applying the NER model (Romero-Fresco 2011). The results provide, on the one hand, data on the accuracy of the subtitles and, on the other hand, information on the correction of errors by the speech recognition software used in an attempt to reconcile accessibility and standardisation in Galician subtitling (Romero-Fresco 2021). Finally, the paper concludes with some suggestions for possible improvements to be made to the speech recognition machine in order to accomplish the acceptable threshold of quality and, therefore, provide equal access for deaf and hard-of-hearing viewers.